In silico guided reconstruction and analysis of ICAM-1-binding var genes from 1 Plasmodium falciparum - Carrington, E; Otto, T; Szestak, T; Lennartz, F; Higgins, M; Newbold, C; Craig, A (Nature Publishing Group, 2018)
The Plasmodium falciparum variant surface antigen PfEMP1 expressed on the surface of infected erythrocytes is thought to play a major role in the pathology of severe malaria. As the sequence pool of the var genes encoding PfEMP1 expands there are opportunities, despite the high degree of sequence diversity demonstrated by this gene family, to reconstruct full-length var genes from small sequence tags generated from patient isolates. To test whether this is possible we have used a set of recently laboratory adapted ICAM-1-binding parasite isolates to generate sequence tags and, from these, to identify the full-length PfEMP1 being expressed by them. In a subset of the strains available we were able to produce validated, full-length var gene sequences and use these to conduct biophysical analyses of the ICAM-1 binding regions.